Create the Video Subtitles Based on Voice Recognition Technology: Test for Some Programs at VTV - Nguyen, Hữu Phong; Vo, Nguyễn Quốc Bảo; Tran, Minh Trung (Journal of Technical Education Science, 2022)
This paper presents the trial results of Speech-To-Text (STT) recognition tool for VOD (Video On Demand) contents of the VTVgo system at Vietnam Television. In order to evaluate the accuracy of the STT tool, the word error rate (WER) was used to measuring the performance of the automatic speech recognition, the machine translation system. Test results of 10 different types of TV show with 1065 video hours were analyzed. The WER had achieved low level from 2.8% to 4.3% with some genres of news, 19h, weather forecasts, where the majority of speakers, presenters (MC) read standard voices in the Studio. The dialogue from a speaker, less interference from outside noise. Besides, to illustrating the video subtitle application, we had conducted the test on the VTVgo system, integrated the optional subtitle display tool into the VTVgo app. The test Android platform was Smart TV and SmartPhone, to demonstrating the ability to apply video subtitles on the OTT (Over The Top) - the digital content distribution platform.